SHM_120748_HST_3D Ceramic Pot - Bonnevier, Helena; National Historical Museums (National Historical Museums, 2026)
Photogrammetric 3D model of a ceramic pot from the Middle Ages, collected in the field at Slottsfjärden in Kalmar and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=661

Link to Sök I Samlingarna

https://samlingar.shm.se/object/07E29EAB-C17A-48D6-925E-43243878CB72
Keywords: 3D Model; Museum Object; Archaeology; Archaeology; Photogrammetry; Archaeology/history; History and archaeology; Dynamic Collections; Swedish Middle Ages; Slottsfjärden; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi